Global Student and Talent Flows: Reexamining the Brain Drain Equation - Bhandari, Rajika (International Higher Education, 2019)
At a time when the student mobility landscape is poised to undergo significant changes, this article argues that it is time to revisit the brain drain issue and examine the fundamental ethics, assumptions, and power dynamics that underpin student mobility, thus ensuring that the mobility of students and talent is based on principles of access, equity, and inclusiveness.